Development of Real-Time Maneuver Library Generation Technique for Implementing Tactical Maneuvers of Fixed-Wing Aircraft - Do hyeon Lee; Chang-Joo Kim; Man Jung Heo; Joo Wan Hwang; Hee Gyeong Lyu; Jun Yeop Lee (International Journal of Aerospace Engineering)
This study develops the real-time maneuver library generation technique for performing aggressive maneuvers of fixed-wing aircraft. Firstly, the general maneuver libraries are defined, and then 7th-order polynomials are used to create the maneuver libraries. The attitude command attitude hold (ACAH) system, the rate command rate hold (RCRH) system, and the speed command speed hold (SCSH) system using the proportional-integral-derivative (PID) control technique are designed to minimize the complexity of the flight control system (FCS) and to reduce the weight and volume of the payload. Moreover, the FCS is used for implementing tactical maneuvers. Finally, flight simulations are implemented for the longitudinal loop and Immelmann-turn maneuvers to check the usefulness of the proposed maneuver library generation technique. This study can affect the development of flight techniques for aircraft tactical maneuvers and the modification of air force operational manuals.